Changes in phenotypic patterns of blood monocytes after kidney transplantation and during acute rejection - Švachová, V; Krupičková, L; Novotný, M; Fialová, M; Mezerová, K; Čečrdlová, E; Lánská, V; Slavčev, A; Viklický, O; Viklický, O; Stříž, I (Physiological research, 2021)
Peripheral blood monocytes, which serve as precursors for tissue macrophages and dendritic cells (DC), play a key role in the immune response to kidney allograft, reparation processes and homeostasis regulation. In this prospective study, we used multicolor flow cytometry to monitor the phenotypic patterns of peripheral monocytes in subjects with uncomplicated outcomes and those with acute rejection. We found a reciprocal increase in the proportion of "classical monocytes" (CD14+CD16-) along with a decline in pro-inflammatory "intermediary" (CD14+CD16+) and "non-classical" (CD14lowCD16+) monocytes in subjects with normal outcomes. In subjects with acute rejection, we observed no reduction in "intermediary" monocytes and no increase in "classical" monocytes. Patients with uncomplicated outcomes exhibited downregulated HLA-DR in all three monocyte subpopulations. However, non-classical monocytes were unaffected in subjects with acute rejection. Expression of CD47 was downregulated after transplantation, while patients with antibody-mediated rejection and donor-specific antibodies showed higher pre-transplant values. In monocytes isolated at the time of biopsy, CD47 expression was higher in individuals with acute rejection compared to patients with normal outcomes one year post-transplant. Expression of CD209 (DC-SIGN) and the proportion of CD163+CD206+ subpopulations were upregulated during the first week after kidney transplantation. CD209 was also upregulated in samples taken on the day of biopsy confirming acute rejection. Our data demonstrate that kidney allograft transplantation is associated with phenotypic changes in peripheral blood monocytes during acute rejection.
Keywords: senioři; rejekce štěpu; senioři nad 80 let; transplantace ledvin; Middle Aged; mužské pohlaví; Prospective Studies; Adult; mladý dospělý; Monocytes; fenotyp; monocyty; Aged, 80 and over; Phenotype; Young Adult; ženské pohlaví; Kidney Transplantation; Graft Rejection; Humans; prospektivní studie; lidé středního věku; dospělí; Female; Aged; lidé; Male